الحماية القانونية للموروث السوسيوثقافي في الإعلام السمعي البصري الجزائري - بصافة, أمينة (My University, 2020)
أمام ميلاد التعددية الإعلامية في الجزائر واختلاف برامجها، وتنوع مالكي القنوات التلفزيونية، هناك مواثيق وقوانين تشمل أخلاقيات المهنة الإعلامية التي تحمي المرسل والمتلقي، خاصة أمام التيار المعولم الذي أصبح يهدد مصير الموروث السوسيوثقافي، هذا الأخير الذي يُفترض على القنوات التلفزيونية عمومية كانت أو خاصة حمايته والارتقاء به، بعيدا عن التيار الثقافي الغربي الذي أصبح المظهر الإعلامي الخاص بالجزائر مرآة عاكسة له، نظرا لعمل الممارسين الإعلاميين على جذب جيوب الممولين والمستثمرين، بحيث تحولت مهام هذه القنوات من مفهوم الخدمة العامة إلى الخدمة الخاصة وهذا ما أدى إلى ضياع حق الجمهور الذي هو من الأساسيات التي تحميها سلطة الضبط. والمتتبع لمحتويات القنوات التلفزيونية على تعددها يلاحظ أنها تعرض برامج مستوردة باستثناء بعض القنوات التي تعتمد على الإنتاج المحلي، رغم أن المادة 46 من قانون السمعي البصري لسنة 2014 نصت على ضرورة التأكد من احترام حصص البرامج مع الحرص أن تكون نسبة 60 بالمائة من البرامج المبثوثة برامج وطنية منتجة في الجزائر، من بينها أكثر من 20 بالمائة مخصصة سنويا لبث الأعمال السمعية البصرية والسينماتوغرافية. وهنا التساؤل حول دور سلطة الضبط في اتخاذ القرارات ومراقبة ما تبثه القنوات الفضائية، بناء على صلاحياتها المتمثلة في ممارسة الرقابة بكل الوسائل المناسبة على موضوع ومضمون وكيفيات برمجة الحصص الإشهارية، والسهر على تطبيق دفاتر الشروط حسب ما نص عليه القانون. وبين المحتوى والرقابة والجمهور والموروث السوسيوثقافي للمجتمع وجب النظر والتحليل في النهج الذي يسلكه البث التلفزيوني انطلاقا من الإشكالية الآتية: ما هي آليات الضبط القانوني للبث التلفزيوني في حماية الموروث السوسيوثقافي للجمهور في ظل تجاوزات الممارسين؟ Abstract: After the pluralism’s media birth in Algeria, which have known recently a different programs, and a normatively diversity of the TV channels’ owners, there are charters and laws, including the ethics of the media profession that protects both sender and receiver, especially in front of the globalized trend that threatens the sociocultural heritage in Algeria, the latter, which is supposed to national television channels either public or private and protect and develop it, especially from the extension of the Western cultural which becomes the reflective model in the appearance Algerian private media, due to the special way of practitioners media to attract the financiers and investors, which lead these channels to shift their services from the concept of public service to the private one, this is what led to the lost of the public's right which is one of the basics that are protected regulatory media authorities. noticing the contents of television channels on multiple find that they were offering imported programs, with the exception of some channels that rely on domestic production, although its content is globalized, despite the fact that the Article 46 of the audiovisual Algerian law for the year 2014 stated the respect for the part programs while taking 60 % for broadcasting national programs produced in Algeria, including more than 20 % annually dedicated for the audio-visual and cinematographic broadcast. paying intension to a potential question of the role of the regulatory media authorities decisions to control the whole broadcasts satellite channels, based on its powerful authorities to protect by all means the content and modes of programming the advertising spots, by the application of the books of conditions according to the law. and between the content, the media control, the public, and sociocultural heritage of community we must consider on the analysis and the approach being followed by television broadcasts by this problematic : What are the legal mechanisms of the television broadcasting to protect the audience’s sociocultural heritage since the practitioners’ omission ?
Keywords: محتوى برامج وسائل الإعلام ؛ الموروث السوسيوثقافي ؛ سلطة ضبط السمعي البصري ؛ الرقابة